Papel do ferro na infecção experimental por Toxoplasma gondii - Oliveira, Mário Cézar (2018)
Many microorganisms have developed the ability to acquire iron from their host to their own metabolism. Toxoplasma gondii, an obligate intracellular parasite, produces rhoptry proteins that are capable of binding to the iron transporter. In addition, iron chelator was able to control parasitism in rat intestinal cells. Therefore, the objective of this work was to investigate the relationship of the effect of iron addition or deprivation on the multiplication of T. gondii and the result of infection when the parasite is administered orally and in cell culture. C57BL/6 mice were orally infected with T. gondii and treated with an iron chelator, deferoxamine or iron supplemented and parasitism, immunological and histological parameters were analyzed. It was observed that the infection increased the deposition of iron in the small intestine, lung and liver and also systematically. Treatment with deferoxamine was able to decrease iron levels in the serum samples. Treatment with deferoxamine reduced parasite burden in the small intestine and inflammatory changes in the organ, preserving its length and also decreased pulmonary parasitism. In addition, iron supplementation increased parasite burden in the small intestine, lung and liver, associated with inflammatory changes in these organs, as well as increased parasite proliferation in cell culture with Caco-2 cells. Oral infection modulated the expression profile of iron absorption markers, increasing systemic IL-6 levels. Together, our results suggest that iron chelation commonly used to treat iron overload may be a promising drug to control T. gondii proliferation and consequently inflammation caused by infection and that iron is an essential nutrient for the metabolism of T. gondii.